Idiom bahasa Jerman yang berunsur alam dan padanannya dalam bahasa Indonesia - Anagata, Anagata; Widodo, Pratomo (Journal of Culture, Literature and Foreign Language Teaching, 2024)
Penelitian ini bertujuan untuk mendeskripsikan (1) persamaan dan perbedaan idiom bahasa Jerman dan idiom bahasa Indonesia yang berunsur alam dan (2) unsur budaya yang melatarbelakangi persamaan dan perbedaan idiom bahasa Jerman dan idiom bahasa Indonesia yang berunsur alam. Penelitian ini merupakan penelitian deskriptif kualitatif. Subjek penelitian ini adalah idiom bahasa Jerman dan idiom bahasa Indonesia yang tedapat dalam kamus idiom bahasa Jerman dan idiom Bahasa Indonesia. Objek penelitian ini adalah unsur alam yang terdapat pada idiom bahasa Jerman dan idiom bahasa Indonesia. Data dianalisis menggunakan metode agih dan padan. Hasil penelitian ini, yaitu terdapat (1) persamaan dan perbedaan idiom bahasa Jerman dan idiom bahasa Indonesia yang berunsur alam, kemudian dibagi menjadi tiga bagian yang terdiri dari (a) persamaan idiom bahasa Jerman dan idiom bahasa Indonesia yang berunsur alam dari segi frasa dan makna sama terdapat enam data, (b) persamaan dan perbedaan idiom bahasa Jerman dan idiom bahasa Indonesia yang berunsur alam dari segi frasa berbeda dan makna sama terdapat 16 data, dan (c) persamaan dan perbedaan idiom bahasa Jerman dan idiom bahasa Indonesia yang berunsur alam dari segi frasa sama dan makna berbeda terdapat tiga data. (2) Unsur budaya yang melatarbelakangi persamaan dan perbedaan idiom bahasa Jerman dan idiom bahasa Indonesia yang berunsur alam ada dua, yaitu pola pikir dan kebiasaan makan dan minum. The nature-based German idiomatic expressions and their Indonesian equivalents Abstract: This research aimed at describing (1) the similarities and differences of the nature based between German idiomatic expressions and Indonesian idiomatic expressions, and (2) the cultural based which the background of the similarities and differences in the use of based nature between German idiomatic expressions and Indonesian idiomatic expressions. This research is a descriptive qualitative. The subject of this research is German idiomatic expressions and Indonesian idiomatic expressions which found in the German and Indonesian idiomatic dictionaries. The object of this research is the nature based found in German and Indonesian idiomatic expressions. Data were analysed using agih and padan method. The results of this research are (1) there are similarities and differences of the nature based between German idiomatic expressions and Indonesian idiomatic expressions, then divided into three parts, namely (a) the similarities of the nature based between German idiomatic expressions and Indonesian idiomatic expressions from same meaning and phrase is six data, (b) the similarities and differences of the nature based between German idiomatic expressions and Indonesian idiomatic expressions from same meaning and difference phrase is 16 data, and (c) the similarities and differences of the nature based between German idiomatic expressions and Indonesian idiomatic expressions from difference meaning and same phrase is three data. (2) Cultural based which the background of similarities and differences in the use of nature based between the German idiomatic expressions and Indonesia idiomatic expressions is two, namely the mindset and eating and drinking habits.